Occurrence and Pathological Observations of Avian Gout in Kerala - Dhanush Krishna, B; Jessil Joseph; Sajitha, I.S; Devi, S.S; K.S. Prasanna (The Indian Veterinary Journal, 2024)
The goal of the current study is to investigate the occurrence and pathological alterations of avian gout in Kerala. We gathered and analysed data on avian gout from August 2016 to June 2022. About 16,036 poultry carcasses were studied and 45 cases were diagnosed as gout based on gross and histopathological lesions. It was found that overall mortality was 0.28% for 6 years, 42.22% of all gout cases were observed during the winter months. The Gramasree breed was the most susceptible breed with a 37.7% incidence rate and the highest incidences (42.22%) were observed in birds older than 5 months.